Benefit reentitlement conditions in unemployment insurance schemes - Andersen, Torben; Strom Kristoffersen, Mark; Svarer, Michael (Bonn, 2015)
"Unemployment insurance schemes include conditions on past employment history as part of the eligibility conditions. This aspect is often neglected in the literature which primarily focuses on benefit levels and benefit duration. In a search-matching framework we show that benefit duration and employment requirements are substitute instruments in affecting job search incentives and thus gross unemployment. We analyse the optimal design of the unemployment insurance system (benefit levels, duration and employment requirements) under a utilitarian social welfare function. Simulations show that a higher insurance motive captured by more risk aversion implies higher benefit generosity and more lax employment requirements but also shortened benefit duration."